The Atlantic Meridional Overturning Circulation and the subpolar gyre observed at the A25-OVIDE section in June 2002 and 2004 - Lherminier, Pascale; Mercier, Herle; Huck, Thierry; Gourcuff, Claire; Perez, Fiz F.; Morin, Pascal; Sarafanov, Artem; Falina, Anastasia (Deep Sea Research Part I: Oceanographic Research Papers, 2010)
The horizontal circulation of the subpolar gyre and the Meridional Overturning Circulation (MOC) are investigated here by comparing two snapshots of the North Atlantic as delivered by two hydrographic sections between Greenland and Portugal. The corresponding cruises were carried out in June–July 2002 and June–July 2004 on R/V Thalassa within the framework of the Ovide project. The absolute transports in June 2004 are described in detail, and then compared with transports in June 2002. The MOC (in density coordinates), driven by the volume balance between the northward North Atlantic Current (NAC) and the net southward export of dense water from the subpolar gyre, did not change: View the MathML source (1 Sv=106 m3 s−1). Its upper limb, above σ1=32.1, is decomposed into two main branches, the Eastern NAC (ENAC) and the Western NAC (WNAC), that transport about 8 Sv each. In the lower limb of the MOC, we find a 4–5 Sv increase in the cyclonic circulation of the subpolar gyre between June 2002 and 2004, affecting mainly the intermediate water without changing the MOCσ amplitude. Accordingly, the 14±2 Sv transport over Reykjanes Ridge in June 2004 (between 58ring operator50′N and Iceland) is estimated to have been 4–5 Sv stronger than in June 2002. Sustaining this observation, a relatively warm and salty anomaly coming from the Iceland Basin was found in the East Greenland-Irminger Current (EGIC) in June 2004, along with a modified vertical structure of the transport that shows a 4–5 Sv intensification of the net southward flow in the corresponding layer. Overall, in June 2004, the EGIC (from the surface to σ0=27.8) is found at 23.7±1.4 Sv in June 2004, and the Deep Western Boundary Current (DWBC) below sums up to 11.2±1.7 Sv, so that the western boundary current is View the MathML source stronger than in June 2002.